On the nexus between exchange rate and income distribution in Turkey: ARDL bound testing analysis - Arif Eser Güzel; Ünal Arslan (Universitas Islam Indonesia, 2019)
If we talk about the importance of variables in economic development, income distribution is not the second to economic growth, especially in emerging countries. These emerging countries are generally characterized by the volatility of exchange rates, especially after most of the countries adopted floating exchange rates system. This paper investigates the impact of an increases in dollar value on income distribution using annual data in the period 1990-2016 for Turkey via an ARDL model and bound testing analysis. In constructing the empirical model, it also considers the impact of GDP per capita on the dependent variable. Findings/Originality: The paper finds that an increase in dollar value leads to a more unequal income distribution in Turkey. The dollar holds an important place in Turkey’s foreign trade. Therefore, the changes in the value of dollar results in significant welfare effects